Transcultural Spirituality: The coping mechanisms of Refugees and Asylum Seekers: A Grounded Theory Study - Murgatroyd, Tamaryn (2013)
There is evidence in the literature to suggest that Spirituality and Culture are neglected in nursing care (Greenstreet, 1999, Fernando, 2004). This has been attributed to lack of understanding and knowledge of how to deliver appropriate spiritual and cultural care, possibly due to the ambiguity of the two concepts. Refugees and Asylum Seekers appear to be vulnerable to mental health problems due to the experiences that they have had, and the lack of social support that they receive in the UK (Fazel et al 2005, Burnett and Peel, 2001). However, they have also been noted to be resilient and resourceful in their coping mechanisms (Bernardes et al, 2012). There is evidence to suggest that spirituality is integral to methods of coping (Strijk et al, 2010). Individual interviews were carried out in order to gain a story from the refugees and asylum seekers that may induce a greater understanding on how they cope with their situation. This, will in turn, increase cultural awareness and understanding of how spirituality can manifest within different cultures to provide a knowledge-base for nursing practice. Findings supported the notion that refugees and asylum seekers are particularly vulnerable to mental health issues. They also highlighted ways in which the refugees and asylum seekers coped. In the grounded theory approach, current theories and were used to provide rationale for different ways in which the refugees felt and acted. Social identity, the concept of control, and coping mechanisms were drawn upon to introduce new theories specific to the asylum seekers and refugees. Nurses can use these findings to understand more about how spirituality can be a coping mechanism to people in mental distress, and different ways in which these coping mechanisms can manifest across cultures to inform nursing care.